Development of Student Worksheets on Thermochemistry Material Based on Problem-Based Learning (PBL) for Phase F - Pong, Anjela A.; Hayon, Vinsensia H.B.; Boelan, Erly Grizca (Universitas Nusa Cendana, 2025)
This study aims to evaluate the validity of Student Worksheets (LKPD) in thermochemistry material designed using a Problem-Based Learning (PBL) approach, assess the implementation of learning using the PBL model, and examine students’ responses to the developed worksheets. The research employed the 4-D development model, although it was limited to the development stage only. The study involved 26 students from class XI.3 at SMA Negeri 1 Semau Selatan as the research subjects. Data collection methods included interviews, validation, and the distribution of questionnaires. The results of the study revealed that: (1) the developed Student Worksheets was considered highly valid, with average scores from material expert validators I and II at 93,05% and 98,6%, respectively, and from media expert validators I and II at 91,65% and 94,45%, respectively; (2) all aspects of classroom learning using the PBL model were implemented successfully; and (3) students’ responses to the LKPD were very positive, with an average score of 90%.